Pengaruh Prosedur Kerja, Kompetensi dan Kepuasan Kerja Terhadap Produktivitas Kerja Pegawai Madrasah Ibtidaiyah Negeri 9 Kota Banda Aceh - Baihaqi Baihaqi; Moch Syauki; Syarifuddin syarifuddin; Bukhari Usman (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
The aim of this research is to determine the magnitude of the influence of work procedures, competence and job satisfaction on the work productivity of employees at Madrasah Ibtidaiyah Negeri 9 Banda Aceh City. This research uses a quantitative approach using primary data through questionnaires. The total population is 52 employees and the sample in this study is a population sample of 52 employees. Based on the results of the hypothesis test, it is known that in the partial test, the t-count value for Work Procedures is 1.834, which is greater than the t-table of 1.677, so that the Ha hypothesis is accepted and shows that Work Procedures have an effect on the Work Productivity of Madrasah Ibtidaiyah Negeri 9 Banda Aceh City employees. For the Competency variable, the calculated t-value of 1.939 also exceeds the t-table of 1.677, so that Ha is accepted, indicating that Competence has an effect on Work Productivity. Apart from that, the t-calculated value for Job Satisfaction is 3.861, which is higher than the t-table of 1.677, so Ha is accepted, which means Job Satisfaction also influences Work Productivity. In the simultaneous test, the F-count value of 5.158 is greater than the F-table of 2.800, which shows that together, Work Procedures, Competencies and Job Satisfaction have a significant effect on employee work productivity.